Implementation of a peer support worker in a forensic psychiatric hospital in Germany—Views of patients - Walde, Peggy; Hadala, Julia; Peipe, Verena; Völlm, Birgit Angela (Frontiers in Psychiatry, 2023)
Peer Support has become common in psychiatric practice in the past decade. In this article we present findings from the implementation of peer support service into a forensic mental health hospital for offenders with substance use disorders from a patient’s perspective. We conducted focus groups and interviews with patients of the clinic to explore their experiences, acceptance and perceived effect of the peer support service. Data collection was conducted in two different points in time, three months and twelve months after the introduction of the of some peer support intervention. In the first time point two focus groups involving 10 patients and three semi-structured individual interviews were conducted. The second time point included one focus group with five patients and five semi-structured individual interviews. All focus groups and individual interviews were audio recorded and transcribed verbatim. Data analysis was conducted using thematic analysis. Five themes emerged, 1) attitudes towards the concept of peer support work and the peer support worker himself; 2) Activities and conversation topics; 3) experiences and effects; 4) Peer support in contrast to other professions; and 5) ideas and wishes for future peer support in the clinic. In general, patients agreed on the high value of peer support work. Findings revealed a broad acceptance of the peer support intervention by most patients, but also some reservations. They saw the peer support worker as someone who is part of the professional team, and has a unique knowledge coming from personal experience. This knowledge often facilitated conversations about several topics related to patients experiences with substance use and their recovery journey.